Implementation of a Camera Sensor Pixy 2 CMUcam5 to A Two Wheeled Robot to Follow Colored Object - Sigit Dani Perkasa; Prisma Megantoro; Hendra Ari Winarno (Journal of Robotics and Control (JRC), 2021)
This article discusses the design of a colored object follower robot. The colored object used has a simple shape. For the detection process, a wheeled robot that uses sensors based on digital images of Pixy 2. Pixy2 can learn to detect objects that you teach it, just by pressing a button.  Additionally, Pixy2 has new algorithms that detect and track lines for use with line-following robots. Pixy2 camera is able to recognize and track all objects whose color has been memorized. In maneuvering, this robot has 2 wheels on the right and left. Movement control is carried out by the Arduino Uno microcontroller board. This robot moves according to the direction of movement of the object. The conclusion obtained in this research is that this wheeled robot can be examined from the left, front and right side objects properly, then it follows the direction of the detected object.